IMPLEMENTASI RESTORATIVE JUSTICE BERDASARKAN DISKRESI KEPOLISIAN TERHADAP TINDAK PIDANA KECELAKAAN LALU LINTAS DI POLRES KARANGASEM - I Komang Seri Pande Wahyu; Ni Putu Rai Yuliartini; Muhamad Jodi Setianto (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2022)
This study aims to find out (1) the implementation and constraints as well as the supporting factors for holding restorative justice for traffic accident criminals in the jurisdiction of the Karangasem Police, (2) the discretionary process for traffic accidents at the Karangasem Police based on Law Number 22 of 2009 concerning Road Traffic and Transportation. This type of research uses empirical juridical methods. The sampling technique used was purposive sampling. The techniques used in this research are document study techniques, interview techniques and observation techniques. The data collected were analyzed descriptively qualitatively. The results of the study show (1) the application of retorative justice is an effort to divert from the criminal justice process out of the formal process to be resolved through deliberation and the obstacles faced in implementing restorative justice are that all Polsek in Karangasem Regency do not all have accidents, so if there is an accident managed directly by the Karangasem Police, the supporting factors for holding a retorative justice are that both parties involved, both the victim and the suspect, want to hold a retorative justice, (2) based on an interview from Mr. Gusti Lanang Putu as Head of Traffic at the Karangasem Police, stated that the discretionary process for criminal acts The traffic accident at the Karangasem Police Station was the first for both parties to make a letter of peace, the two parties wanted peace through the penal mediation route.